Analisis Perlindungan Hukum Bagi Pemegang Hak Merek Dagang Ikea Atas Penghapusan Merek Dagang (Antara PT Inter IKEA Swedia vs PT Ratania Khatulistiwa) - Harum, Vanessa Mathilde; Lie, Gunardi; Syailendra, Moody R. (Wajah Hukum, 2023)
Brands play a very important role in the world of marketing because people often associate the quality or reputation of goods and services with certain brands. One of known brands that people are familiar with is IKEA. So the author is interested in analyzing the dispute that occurred between PT Inter IKEA Sweden and PT Ratania Khatulistiwa, especially in the section on When IKEA Sweden Lost Its Brand Rights According to Law Number 15/ 2001 Concerning Brands, and How Legal Protection for the Holders of IKEA Trademark Rights.. Method The approach used in this study is a normative legal approach which refers to the applicable laws and regulations. The protection of the IKEA trademark dispute as a result of not using the IKEA trademark for 3 consecutive years.